The benefits of Heart Rate Variability (HRV) in the assessment of health and exercise performance - Dan Tao; Yeheng He; Alistair Cole; Roger Awan-Scully; Rashmi Supriya; Yang Gao; Julien S Baker (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2022)
The purpose of this brief report is to stimulate further interest and to raise awareness in relation to the usefulness of assessing cardiac autonomic nerve function using heart rate variability (HRV). The paper outlines the mechanisms associated with HRV and the relationships between HRV, health, and athletic performance. The paper then summarizes the potential benefits of HRV in the assessment of health and exercise adaptations. The paper also provides suggestions about the practical implications of HRV measurement during data collection. We hope that the content provides useful information for the application of HRV for health evaluation and training adaptations. In addition, we hope the paper will provide a better understanding of how HRV measurements can be interpreted and used. Finally, the paper provides practical applications that are effective in the assessment of health and athletic training program outcomes.